Dampak Overthinking pada Pelajar di Era Digital dan Strategi Penanganannya dalam Konseling Islam - Miftahul Huda Imaduddin; Ahmad fauzan; Muhammad Musleh (Pascasarjana Universitas Qomaruddin, 2026)
This study aims to analyze the impact of overthinking on students in the digital era and to formulate strategies to address it through an Islamic counseling approach. The method used is qualitative research with a systematic literature review approach, examining various sources such as national and international journal articles, educational psychology books, and Islamic normative sources including the Qur’an and Hadith. The results show that overthinking in students is influenced by internal factors, such as anxiety and negative thinking patterns, as well as external factors, especially exposure to digital media and social media that encourage unhealthy social comparison. The impacts include mental health problems, such as stress and anxiety, as well as decreased concentration and academic performance. From the perspective of Islamic counseling, overthinking is related to a condition of doubt (was-was) and a lack of trust in God (tawakal). Therefore, the proposed strategies include an Islamic cognitive approach, strengthening spirituality through dhikr and prayer, and behavioral management such as limiting the use of digital media. Thus, Islamic counseling provides a more holistic approach by integrating cognitive and spiritual aspects. The implication of this study highlights the importance of integrating Islamic value-based counseling and digital literacy in the education system.